Numerical modelling for hydrodynamic behavior of round shape FLNG interacting with LNG carrier - Siow, Chee Loon (2016)
The diffraction potential theory is an efficient and accurate method to predict the hydrodynamic characteristic of a large floating structure. However, this theory under-estimates the damping coefficient as the viscous effect is ignored. This weakness causes the diffraction potential theory to be less accurate in predicting the motion of floating structure in damping dominant region. Therefore, this research aims to propose a method to improve the estimation of hydrodynamic characteristic of free floating round shape Floating Liquefied Natural Gas (FLNG) carrier when it is alone and when it is interacting with another structure which is arranged in parallel head-sea condition. The proposed method was developed by modifying the diffraction potential theory and improving with the application of drag equation. The proposed method was also further developed by using motion’s energy dissipation concept and Huygens Principle to predict the influence of wave generated by the motion of nearby structure to the response amplitude operator (RAO) of the FLNG. To validate the proposed method, motion experiments in regular wave were conducted in selected conditions. Comparative study was also conducted by using FLNG’s RAO result predicted by ANSYS AQWA software. Over-estimation of peak heave RAO of single FLNG case is reduced from 2.42 to 1.74 by the proposed method as the method considered the viscous damping in its calculation. In interaction cases, the peak heave RAO is increased to 2.1 due to the effect of radiating waves. Besides, the interaction effect also induces sway and roll motion. The peak sway RAO estimated by both proposed method and experiment is around 0.22. The interaction effects on heave RAO and roll RAO are stronger around the motions' natural period as the damping coefficients are reduced around motion natural period. The research results showed that the proposed method improved the accuracy of the simulation by reducing the amount of over-prediction on the floating structure’s RAO in damping dominant region.